United Republic of Tanzania : 2009 Article IV Consultation, Fifth Review Under the Policy Support Instrument, Request for a Twelve-Month Arrangement Under the Exogenous Shocks Facility, and Request for an Extension of the Policy Support Instrument; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for United Republic of Tanzania. (IMF Staff Country Reports; Country Report, 2009)
Tanzania's banking system remains sound but is vulnerable to credit risk resulting from the economic slowdown. This staff report examines Tanzania's 2009 Article IV Consultation, fifth review under the Policy Support Instrument, and request for a Twelve-Month Arrangement under the Exogenous Shocks Facility. The authorities have taken steps to maintain financial sector stability, including comprehensive and regular analysis of risks to the sector. Tanzania's balance of payments is under pressure, and reserves are declining.